A comparative analysis of physiological and functional effectiveness of speech and music perception among musicians and non-musicians. (1st October 2020) - Xu, Zhibin; Yuan, Bo; Zhernovnykova, Oksana; Zelenska, Liudmyla
ABSTRACT: The purpose of the study is to compare at the physiological and functional levels, the effectiveness of speech and music perception among musicians and non-musicians. The study was conducted in 2018 in Ningbo University in Zhejiang Province (China) on 235 students aged 20-21. The results showed that in the experimental group, when perceiving music, symmetrical hemisphere interaction parameters dominate ( p ≤ 0.05), in both groups, right-hand parameters dominate in speech perception. The third group showed a difference in the depth of decrease in the amplitude of the alpha rhythm with respect to the resting state ( p ≤ 0.03) in the low-frequency range when listening to a fragment of Slavic folklore. The interaction of the cerebral hemispheres determines a high result in the processing of music. The latter manifested itself when listening to Slavic music: the width of the alpha-1 range is wider when listening in comparison with the state of rest.